Luminescent lanthanide-alginate fiber as well as preparation method and application thereof

Lanthanide-alginate fibers were prepared by wet spinning technology, and cross-linked with lanthanide ions with sodium alginate and 2,2'-bipyridine, the luminescent anti-counterfeiting materials in the prior art were solved in color purity and light-resistant stability in the prior art. The problem of quality and cost is that low-cost, long-life multi-color fluorescent fiber is realized, suitable for flexible anti-counterfeiting technology, and provides rich anti-counterfeiting and data encryption strategies.

CN119194663APending Publication Date: 2024-12-27QINGDAO UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411329783.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing luminescent anti-counterfeiting technologies are difficult to meet strict requirements in evaluating high color purity, photobleaching resistance and long-term stability, and the safety and reliability requirements of flexible wearable devices have driven the demand for advanced flexible anti-counterfeiting technologies, but traditional methods and processes Complex, high cost, poor economic benefits.

Method used

Wet spinning technology is used to prepare lanthanide-alginate fibers. Lanthanide ions act as ion crosslinking agents and luminescent agents at the same time, and fibers are formed by crosslinking with sodium alginate and 2,2'-bipyridine, according to different terbium and The molar ratio of europium emits red, orange and green fluorescence under 254 nanometers of ultraviolet light, and regulates fluorescence characteristics under acidic, alkaline environment and iron ion stimulation.

Benefits of technology

It realizes low-cost, easy-to-manufacturing and long fluorescence life, and can be woven into diverse anti-counterfeiting patterns, providing rich anti-counterfeiting effects and flexible application potential, and fluorescence characteristics can be effectively quenched under external conditions and recover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194663A_ABST
    Figure CN119194663A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lanthanide series-alginate fibers, and particularly relates to a luminous lanthanide series-alginate fiber as well as a preparation method and application thereof. Sodium alginate and LnCl3 are used as raw materials, and the composite material is prepared through a wet spinning process and has red, orange and green fluorescence emission. The preparation method comprises the following steps: putting a sodium alginate aqueous solution into a spinning injector, extruding the sodium alginate aqueous solution into a coagulating bath containing LnCl3 and 2, 2 '-dipyridyl, quickly generating hydrogel fibers after the spinning solution is in contact with the coagulating bath, taking the fibers out of the coagulating bath, and air-drying the fibers at normal temperature to obtain the lanthanide-alginate fibers. The lanthanide-alginate fiber disclosed by the invention can emit red, orange and green fluorescence according to different doping proportions of lanthanide elements, has good formability, thermal stability and homogeneity, and shows huge application potential in the field of flexible anti-counterfeiting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lanthanide-alginate fibers, and in particular relates to a luminescent lanthanide-alginate fiber and a preparation method and application thereof. Background Art

[0002] Anti-counterfeiting technologies, including holograms, radio frequency identification, plasma tags, quick response codes, barcodes, and luminescent anti-counterfeiting technologies. Luminescent anti-counterfeiting technology can hide patterns without external stimulation, but can display unique optical information under specific lighting or other excitation conditions, thereby providing a highly secure, diverse, and intelligent encryption method. The key to improving luminescent anti-counterfeiting technology lies in the selection of appropriate luminescent materials and carefully designed anti-counterfeiting strategies. Materials such as carbon quantum dots, semiconductor quantum dots, chalcogen compounds, and organic dyes are considered to be strong candidates for luminescent anti-counterfeiting. However, when evaluating strict requirements such as high color purity, resistance to photobleaching, and continuous long-term stability, these materials often fail to meet the requirements.

[0003] With the development of technology, flexible wearable devices are becoming increasingly popular due to their comfort and convenience. It has become crucial to ensure the safety and reliability of these devices, which in turn drives the demand for advanced flexible anti-counterfeiting technologies. At present, the preparation methods of doped lanthanide fibers include producing lanthanide-containing silk, surface treatment of aramid fibers to introduce lanthanides, and incorporating lanthanide complexes into fiber-forming polymers. However, these methods often lead to complex processes, increased costs, and reduced economic benefits. Sodium alginate is a natural polysaccharide with the advantages of biodegradability, biocompatibility, non-toxicity, and low cost. In the presence of divalent or trivalent metal cations, sodium alginate can form stable hydrogels by cross-linking or be processed into fibers by spinning.

[0004] Therefore, there is an urgent need to develop a lanthanum anti-counterfeiting fiber that takes into account both manufacturing cost and preparation difficulty as well as anti-counterfeiting effect. Summary of the invention

[0005] In view of the problems of the prior art, the present invention provides a luminescent lanthanide-alginate fiber and a preparation method thereof. Lanthanide ions act as both ionic crosslinking agents and luminescent agents, and alginate is crosslinked with lanthanide ions to form fibers. The luminescence of lanthanide ions is sensitized by the ligand 2,2'-bipyridine, and red, orange and green fluorescence are emitted under 254 nanometer ultraviolet light according to the different molar ratios of doped lanthanide ions, providing a new direction for the application of lanthanide fibers in flexible anti-counterfeiting technology.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a luminescent lanthanide-alginate fiber, which is prepared by a wet spinning process using sodium alginate and LnCl3 as raw materials. The fiber is cylindrical, has no cracks on the surface, has multiple pores in the cross section, and has red, orange and green fluorescence emission.

[0007] Furthermore, the fiber contains terbium and europium at different molar ratios.

[0008] A method for preparing luminescent lanthanide-alginate fibers.

[0009] The sodium alginate aqueous solution is loaded into the spinning syringe and extruded into a coagulation bath containing LnCl3 and 2,2'-bipyridine at an extrusion rate of 2 mL / min. Hydrogel fibers are rapidly generated after the spinning solution contacts the coagulation bath. After about 2 minutes, the fibers are taken out of the coagulation bath and air-dried at room temperature to obtain lanthanide-alginate fibers.

[0010] Furthermore, the molar ratio of terbium / europium in LnCl3 is 0:10, 3:7 or 10:0.

[0011] Furthermore,

[0012] The concentration of the sodium alginate aqueous solution is 1 wt %, and the concentration of LnCl 3 and 2,2'-bipyridine is 10 mM.

[0013] Furthermore,

[0014] The inner diameter of the spinning syringe is 0.7 mm.

[0015] Application of multicolor luminescent lanthanide-alginate fibers with multiple stimulus responses,

[0016] The fiber is used for anti-counterfeiting, including flexible anti-counterfeiting.

[0017] Fibers with three different Tb / Eu molar ratios of 0:10, 3:7 or 10:0 exhibited red, orange and green fluorescence under 254 nm UV light.

[0018] Furthermore,

[0019] The luminescence of the fiber is weakened when it is exposed to an acidic environment, and is restored in an alkaline environment.

[0020] Furthermore,

[0021] The fibers luminesce less when exposed to ferric ions.

[0022] The benefits of the present invention are:

[0023] The present invention uses wet spinning technology to develop a luminescent lanthanide-alginate fiber that can be used for anti-counterfeiting. These fibers not only show good formability, thermal stability and homogeneity, but also emit red, orange and green fluorescence according to different doping ratios of lanthanide elements under 254 nanometer ultraviolet light. Compared with traditional organic dyes, the fibers have a longer fluorescence lifetime. The fibers can be woven into a variety of anti-counterfeiting patterns. Moreover, under the stimulation of external conditions, their fluorescence properties can be effectively quenched and restored, thereby providing a richer anti-counterfeiting effect. Due to its low cost, easy manufacturing and high flexibility, lanthanide-doped fibers show great application potential in the field of flexible anti-counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The fluorescence photographs of lanthanide-alginate microspheres with different terbium / europium molar ratios under an excitation wavelength of 254 nanometers in the embodiments of the present invention are shown;

[0025] Figure 2 a is the fluorescence spectra of lanthanide-alginate microspheres with different terbium / europium molar ratios in the embodiments of the present invention;

[0026] b is the International Commission on Illumination chromaticity diagram coordinate corresponding to the embodiment of the present invention;

[0027] Figure 3 1 is the excitation spectra of lanthanide-alginate microspheres with different terbium / europium molar ratios in the embodiments of the present invention;

[0028] Figure 4 This is a fluorescence photograph of lanthanide-alginate microspheres without bipyridine added under an excitation wavelength of 254 nanometers in an embodiment of the present invention;

[0029] Figure 5 The photos of the terbium / europium-sodium alginate fibers in wet and dry states are shown in the examples of the present invention;

[0030] Figure 6 The scanning electron microscope images and elemental mapping of different lanthanide-alginate fibers after freeze drying according to the embodiments of the present invention;

[0031] (a, b, d, e) SEM images of terbium / europium-alginate fibers;

[0032] (g,h) SEM images of terbium-sodium alginate fibers.

[0033] (j, k) SEM images of europium-alginate fibers;

[0034] (c,f) Elemental mapping of terbium / europium-alginate fibers.

[0035] (i) Elemental mapping of terbium-alginate fibers,

[0036] (l) Elemental mapping of europium-alginate fibers;

[0037] Figure 7 a is the FTIR spectra of sodium alginate, europium-sodium alginate fiber, terbium / europium-sodium alginate fiber and terbium-sodium alginate fiber in the embodiments of the present invention;

[0038] b is the thermogravimetric and differential thermogravimetric curves of terbium / europium-sodium alginate fiber according to an embodiment of the present invention;

[0039] c is the stress-strain curve of the terbium / europium-sodium alginate fiber of the embodiment of the present invention;

[0040] Figure 8 The fluorescence spectra and luminescence characteristics of different lanthanide-alginate fibers of the embodiments of the present invention are shown;

[0041] (a) Fluorescence spectra of Tb-alginate fiber, (b) Tb / Eu-alginate fiber and (c) Tb-alginate fiber under 254 nm excitation. (d) CIE chromaticity coordinates further determine the luminescence color of Tb-alginate fiber, Tb / Eu-alginate fiber and Eu-alginate fiber; (e) Luminescence lifetime of Tb-alginate fiber, Tb / Eu-alginate fiber and Eu-alginate fiber under 254 nm excitation; (f) Intensity ratio of fluorescence peaks of Tb / Eu-alginate fiber at different excitation wavelengths (IRP, I 616 / I 545 );

[0042] Fig. 9 Fluorescence photos of lanthanide-alginate fibers with different terbium / europium molar ratios under an excitation wavelength of 254 nanometers according to the present invention

[0043] Fig.10 The responsiveness of the lanthanide-alginate fiber to environmental stimuli in the embodiment of the present invention;

[0044] (a) Schematic diagram of the quenching and recovery process of fluorescence by hydrochloric acid atmosphere and ammonia atmosphere. (b, c) Reversible quenching and recovery of fluorescence of terbium / europium-alginate fibers by hydrochloric acid atmosphere and ammonia atmosphere. (d) Schematic diagram of fluorescence quenching induced by iron ions. (e) Selective fluorescence quenching of terbium / europium-alginate fibers by iron ions.

[0045] Fig.11 The photos of (a) terbium-sodium alginate fiber and (b) europium-sodium alginate fiber selectively quenched by metal ion solution treatment according to the embodiment of the present invention are shown;

[0046] Fig.12 a is a photograph of lanthanide-alginate fibers with different terbium / europium molar ratios under natural light and ultraviolet light conditions in the embodiments of the present invention;

[0047] b Four knots woven using different fibers under 254 nm UV light;

[0048] c Pattern “QDU” made of different fibers under natural light and 254 nm UV light;

[0049] d Schematic diagram of the design information encrypted patterns made of different fibers under 254 nm UV light;

[0050] Photo of the multi-flexible anti-counterfeiting of the e-fiber knot under 254nm UV light;

[0051] Fig.13 a is the thermogravimetric (TG) and differential thermogravimetric (DTG) curves of terbium-sodium alginate fiber according to an embodiment of the present invention;

[0052] b is the thermogravimetric (TG) and differential thermogravimetric (DTG) curves of the europium-sodium alginate fiber of the embodiment of the present invention;

[0053] Fig.14 The stress-strain curves of (a) terbium-sodium alginate fiber and (b) europium-sodium alginate fiber in the embodiments of the present invention;

[0054] Fig.15 a is the intensity ratio of the fluorescence emission peak of terbium-sodium alginate fiber under different excitation wavelengths (IRP, I 545 / I 489 );

[0055] b is the intensity ratio of the fluorescence emission peak of the europium-sodium alginate fiber under different excitation wavelengths (IRP, I 616 / I 592 );

[0056] Fig.16 The luminescence lifetime of the terbium-sodium alginate fiber, the terbium / europium-sodium alginate fiber and the europium-sodium alginate fiber in the embodiments of the present invention at the optimal excitation wavelength;

[0057] Fig.17 These are photos of the lanthanide-alginate woven pattern of the embodiment of the present invention illuminated by sunlight and 254 nm ultraviolet light respectively under different material backgrounds;

[0058] Fig.18 These are photos of the lanthanide-alginate woven pattern of the embodiment of the present invention illuminated by sunlight and 254 nm ultraviolet light respectively under different color backgrounds;

[0059] Fig.19 These are photos of fluorescence quenching and recovery of (a, b) terbium-sodium alginate fibers and (c, d) europium-sodium alginate fibers treated with hydrochloric acid and ammonia in an example of the present invention. DETAILED DESCRIPTION

[0060] The specific implementation manner will be further described below in conjunction with the accompanying drawings.

[0061] The reagents and instruments in the following examples are all conventional experimental reagents and instruments.

[0062] Embodiment 1:

[0063] A luminescent lanthanide-alginate fiber is prepared by a wet spinning process using sodium alginate and LnCl3 as raw materials. The fiber is cylindrical, has no cracks on the surface, has multiple pores in the cross section, and has red, orange and green fluorescence emission. Terbium and europium in different molar ratios are contained in the fiber.

[0064] A method for preparing luminescent lanthanide-alginate fibers.

[0065] The luminescent color of lanthanide compounds can be achieved by adjusting their components. After being doped into a polymer matrix, lanthanide compounds can be made into luminescent materials of different shapes, such as microspheres and fibers. The luminescence intensity of lanthanide compounds can be enhanced by adding 2,2'-bipyridine as a co-ligand. In order to determine the optimal components and luminescent color of the fiber, we first conducted experiments on hydrogel microspheres. Preparation of lanthanide alginate hydrogel microspheres:

[0066] In a typical preparation process, 5 mL of sodium alginate aqueous solution (1 wt%) was loaded into a syringe (inner diameter 0.7 mm). Subsequently, the sodium alginate solution was dripped into a solution containing LnCl3 (10 mM; Ln: europium, terbium) and 2,2'-bipyridine (10 mM), and hydrogel microspheres were quickly formed. After about 2 minutes, the microspheres were removed from the solution and air-dried at room temperature for 24 hours. Seven hydrogel microspheres with different terbium / europium molar ratios were prepared.

[0067] Experimental results:

[0068] Figure 1 The fluorescence images of lanthanide-alginate microspheres with different terbium / europium molar ratios under 254 nm excitation wavelength. Figure 2 (a) Fluorescence spectra of lanthanide-alginate microspheres with different terbium / europium molar ratios; (b) The corresponding International Commission on Illumination chromaticity diagram coordinates, with the excitation wavelength being 254 nm. It can be seen that the hydrogel microspheres with terbium / europium molar ratios of 0:10, 3:7 and 10:0 have red, orange and green fluorescence emissions, respectively. Figure 3 The excitation spectra of lanthanide-alginate microspheres with different terbium / europium molar ratios were obtained to determine the effectiveness of 254 nm as an excitation light source. Figure 4 The fluorescence photograph of lanthanide-alginate microspheres without bipyridine added at an excitation wavelength of 254 nanometers is used to confirm that the luminescence effect of lanthanide-alginate luminescent materials can be effectively sensitized by adding ligands;

[0069] Preparation of lanthanide-alginate fibers

[0070] In the wet spinning process, 5 mL of sodium alginate aqueous solution (1 wt%) was loaded into a spinning syringe (inner diameter 0.7 mm). Then, the sodium alginate solution was extruded into a coagulation bath containing LnCl3 (10 mM; Ln: europium, terbium) and 2,2'-bipyridine (10 mM) at an extrusion rate of 2 mL / min. Hydrogel fibers were rapidly generated after the spinning solution came into contact with the coagulation bath. After about 2 minutes, the fibers were taken out of the coagulation bath and air-dried at room temperature for 24 hours to obtain lanthanide-alginate fibers. Three fibers with different terbium / europium molar ratios (0:10, 3:7, and 10:0) were prepared and named europium-sodium alginate fibers, terbium / europium-sodium alginate fibers, and terbium-sodium alginate fibers, respectively.

[0071] Figure 5 The following are photos of Tb / Eu-alginate fibers in wet (left) and dry (right) states. The fibers show good uniformity in both wet and dry states.

[0072] Figure 6 Scanning electron microscope (SEM) images and elemental mapping of different lanthanide-alginate fibers after freeze drying. Among them, (a, b, d, e) SEM images of terbium / europium-alginate fibers; (g, h) SEM images of terbium-alginate fibers, (j, k) SEM images of europium-alginate fibers. (c, f) Elemental mapping of terbium / europium-alginate fibers, (i) Elemental mapping of terbium-alginate fibers, (l) Elemental mapping of europium-alginate fibers. Figure 6 a, d, b, e SEM observations show that the cross section of the terbium / europium-sodium alginate fiber has many pores, while the fiber surface is cylindrical and has no obvious cracks, which helps to improve the wet spinning efficiency and reduce fiber breakage during processing. Figure 6 g,h) and europium-alginate fibers ( Figure 6 j, k) have similar morphologies to those of Tb / Eu-alginate fibers. Figure 6 The elemental mapping of c and f reveals the uniform distribution of terbium and europium in the terbium / europium-alginate fibers. Similarly, in the terbium-alginate fibers and the europium-alginate fibers, e.g. Figure 6 As shown in Figures i and l, terbium or europium is also uniformly distributed throughout the fiber. The uniform distribution of lanthanides is critical to ensure uniform luminescence performance of individual fibers and also demonstrates a reliable wet spinning process, which can effectively ensure the reproducibility of fiber performance in large-scale production.

[0073] Figure 7(a) FTIR spectra of sodium alginate, europium-alginate fibers, terbium / europium-alginate fibers and terbium-alginate fibers, (b) thermogravimetric and differential thermogravimetric curves of terbium / europium-alginate fibers, (c) stress-strain curves of terbium / europium-alginate fibers. In the Fourier transform infrared spectroscopy (FTIR) analysis of lanthanide-alginate fibers, such as Figure 7 As shown in a, the vibration spectrum of pure sodium alginate is at 3268cm -1 The characteristic stretching vibration of hydroxyl (-OH) is shown at 3251 cm. The addition of lanthanide ions causes the -OH stretching vibration peak to move to 3251 cm -1 , which may be due to the interaction between lanthanide ions and hydroxyl groups. In addition, in the Fourier infrared spectrum of pure sodium alginate, at 1593 cm -1 and 1407cm -1 Two significant peaks appeared at 1593cm, representing the antisymmetric and symmetric stretching vibrations of carboxyl groups. The addition of lanthanide elements caused these peaks to shift significantly. -1 The peak at 1578 cm -1 , 1407cm -1 The peak at 1414 cm -1 , indicating that the carboxylate is involved in the coordination with the lanthanide.

[0074] like Figure 7 As shown in Figure b, a comprehensive thermal analysis of the Tb / Eu-alginate fibers was performed to evaluate their thermal stability and decomposition behavior. The first stage of thermal decomposition occurs between 30 °C and 185 °C and is characterized by an initial mass loss of 18.61%, which is attributed to the evaporation of water molecules that are physically adsorbed to the fiber surface or part of the fiber composition. The subsequent thermal decomposition stage lasts from 185 °C to 400 °C, corresponding to a total mass loss of 26.86%. The mass loss is due to the thermal degradation of the alginate chains within the fiber matrix, producing water, carbon dioxide, and hydrocarbon gases as final products. The thermal profiles of the Eu-alginate and Tb-alginate fibers are similar. Therefore, the thermogravimetric and differential thermogravimetric curves indicate that the fibers are highly thermally stable and can be used at temperatures up to 185 °C without significant structural degradation.

[0075] In order to understand the mechanical behavior of Tb / Eu-alginate fibers, tensile tests were performed. The fibers showed excellent tensile properties with a tensile strength of up to 413.54 MPa, which is mainly due to the presence of ionic crosslinks and hydrogen bonds in their structure. In addition, Tb-alginate and Eu-alginate fibers also showed excellent tensile strength. This tensile strength not only reveals the fiber's resistance to breakage, but also indicates their suitability for various processing techniques, which is crucial for the practical application of textiles.

[0076] Fig.13Thermogravimetric (TG) and differential thermogravimetric (DTG) curves of (a) terbium-alginate fiber and (b) europium-alginate fiber. Fig.14 Stress-strain curves of (a) Tb-alginate fibers and (b) Eu-alginate fibers.

[0077] Embodiment 2:

[0078] Application of a luminescent lanthanide-alginate fiber,

[0079] Controllable Luminescence Properties of Lanthanide-Alginate Fibers

[0080] Figure 8 Fluorescence spectra and luminescence properties of different lanthanide-alginate fibers. (a) Fluorescence spectra of terbium-alginate fibers, (b) terbium / europium-alginate fibers, and (c) terbium-alginate fibers under 254 nm excitation. (d) CIE chromaticity coordinates further determine the luminescence colors of terbium-alginate fibers, terbium / europium-alginate fibers, and europium-alginate fibers. (e) Luminescence lifetimes of terbium-alginate fibers, terbium / europium-alginate fibers, and europium-alginate fibers. (f) Intensity ratios of fluorescence peaks of terbium / europium-alginate fibers at different excitation wavelengths (IRP, I 616 / I 545 ), which reflects the color purity of the fiber luminescence.

[0081] The ff transitions of europium and terbium produce strong metal center luminescence after coordination with ligands. Under 254 nm excitation, europium-alginate fibers, terbium / europium-alginate fibers, and terbium-alginate fibers exhibit red, orange, and green fluorescence, respectively. The luminescence color was confirmed by their fluorescence spectra, which matched the CIE chromaticity diagram. Four prominent peaks were observed at 490, 545, 592, and 616 nm, corresponding to terbium ( 5 D4→ 7 F6, 5 D4→ 7 F5) and europium ( 5 D0→ 7 F1, 5 D0→ 7 In addition, the luminescence lifetime of the europium-sodium alginate fiber at 616nm is 0.332ms, the luminescence lifetime of the terbium / europium-sodium alginate fiber at 616nm is 0.718ms, and the luminescence lifetime of the terbium-sodium alginate fiber at 545nm is 1.376ms, which is equivalent to the luminescence lifetime at the optimal excitation wavelength.

[0082] In our fibers, I 616 represents red emission at 616 nm, I 545 represents the green emission at 545 nm; the ratio of these peak intensities I616 / I 545 Indicates the color purity of the fiber's luminescence. Figure 8 f shows an important characteristic of terbium / europium-alginate fibers: IRP is sensitive to the excitation wavelength. When the excitation wavelength is 300 nanometers, I 616 / I 545 The value is 3.3, when the excitation wavelength is 400 nanometers, I 616 / I 545 The value increased sharply to 13.2. In addition, similar excitation-dependent photoluminescence was observed in terbium-alginate fibers and europium-alginate fibers. From these results, lanthanide-alginate fibers are considered to be potentially useful for luminescent anti-counterfeiting.

[0083] Fig.15 (a) Intensity ratio of fluorescence emission peak of terbium-alginate fiber at different excitation wavelengths (IRP, I 545 / cc 489 ); (b) is the intensity ratio of the fluorescence emission peak of europium-alginate fiber (IRP, I 616 / I 592 ).

[0084] Fig.16 It is the luminescence lifetime of terbium-sodium alginate fiber, terbium / europium-sodium alginate fiber and europium-sodium alginate fiber at the optimal excitation wavelength.

[0085] Fig.17 Photographs of lanthanide-alginate weave patterns illuminated by sunlight and 254 nm UV light against different material backgrounds;

[0086] Fig.18 Photographs of lanthanide-alginate weave patterns illuminated by sunlight and 254 nm UV light against different color backgrounds;

[0087] Embodiment 3:

[0088] Application of a luminescent lanthanide-alginate fiber,

[0089] Stimuli-responsiveness of lanthanide-alginate fibers

[0090] Fig.10 Responsiveness of lanthanide-alginate fibers to environmental stimuli. (a) Schematic diagram of the quenching and recovery process of fluorescence by hydrochloric acid atmosphere and ammonia atmosphere. (b, c) Reversible quenching and recovery of fluorescence of terbium / europium-alginate fibers by hydrochloric acid atmosphere and ammonia atmosphere. (d) Schematic diagram of fluorescence quenching induced by iron ions. (e) Selective fluorescence quenching of terbium / europium-alginate fibers by iron ions. In all these experiments, the excitation wavelength was 254 nm. The fluorescence of terbium / europium-alginate fibers weakened when exposed to hydrochloric acid atmosphere, as shown in Figure 2. Fig.10b. The fluorescence intensity of the Tb / Eu-alginate fiber decreased significantly within 1 hour in a hydrochloric acid environment and completely disappeared after 24 hours. After the ammonia atmosphere was reintroduced, the luminescence of the fiber was restored.

[0091] Fig.11 Photographs of (a) Tb-alginate fibers and (b) Tb-alginate fibers selectively quenched by metal ion solution treatment, with an excitation wavelength of 254 nm.

[0092] In contrast, the fibers exhibited stable photoluminescence under alkaline conditions, such as in an ammonia atmosphere, e.g. Fig.10 c. However, when the fibers were initially exposed to an ammonia atmosphere for 24 hours and then placed in a hydrochloric acid atmosphere, the fluorescence no longer recovered. Similar responses were observed for terbium-alginate fibers and europium-alginate fibers. These different responses to acidic and alkaline stimuli highlight their potential for applications in anti-counterfeiting and data encryption.

[0093] Fig.19 Photographs of fluorescence quenching and recovery of (a, b) terbium-alginate fibers and (c, d) europium-alginate fibers treated with hydrochloric acid and ammonia gas, with an excitation wavelength of 254 nm.

[0094] For the fluorescence quenching under acid-base conditions, we proposed the following mechanism: when the fiber is exposed to an acidic atmosphere, the 2,2′-bipyridine ligand is protonated and cannot react with Ln 3+ When the fiber is exposed to alkaline atmosphere, it undergoes deprotonation and recombines with Ln 3+ Coordination, fluorescence recovery.

[0095] The photoluminescence properties of lanthanide-alginate fibers can be tuned by introducing competitive metal ions, e.g. Fig.10 In the experiment, the fiber was immersed in 10 mM solutions of different metal ions, and it was found that only the ferric chloride solution caused a significant quenching of fluorescence, as shown in Figure d. Fig.10 e and Fig.11 As shown. This indicates that the coordination ability of trivalent iron ions with 2,2'-bipyridine is stronger than that of lanthanide ions, which competitively destroys the coordination sphere of lanthanide ions, affects the energy absorption and transfer process, and thus quenches the luminescence of lanthanide ions. This selective response to metal ions, especially the fluorescence quenching of iron ions, shows the application potential of fibers in anti-counterfeiting and sensing technology.

[0096] Embodiment 4:

[0097] Application of a luminescent lanthanide-alginate fiber,

[0098] Flexible anti-counterfeiting of lanthanide-alginate fibers

[0099] Lanthanide-alginate fibers provide a solid foundation for flexible anti-counterfeiting applications due to their rich photoluminescent properties, excellent flexibility, and multiple stimulus responsiveness. Fig.12 (a) Photos of lanthanide-alginate fibers with different terbium / eupium molar ratios under natural light and UV light conditions. (b) Four knots woven using different fibers under 254nm UV light. (c) Pattern “QDU” made from different fibers under natural light and 254nm UV light. (d) Schematic diagram of design information encryption pattern made from different fibers under 254nm UV light. (e) Photo of fiber knot for multiple flexible anti-counterfeiting under 254nm UV light

[0100] like Fig.12 As shown in a, fibers with three different Tb / Eu molar ratios can be wound around the rod and are indistinguishable under daylight but exhibit distinct fluorescent colors (red, orange, and green) under 254 nm UV light. Fig.12 b shows Chinese knots and Fig.12 The “QDU” pattern in c further demonstrates their flexible anti-counterfeiting properties, showing great potential in complex patterns and design versatility.

[0101] The fluorescent properties of the fibers also demonstrate their great potential for complex encryption under monochromatic light. Fig.12 d demonstrates their ability to display different information based on fluorescent colors. Under natural light, the pattern made of fibers shows only the number "8888", while under 254-nanometer ultraviolet light, it shows a complex data array containing the green number "22", the red "04", the composite number "2024" of green and red, and the three-color number "8888". This ability to modulate information through luminescent colors provides a sophisticated strategy for data encryption and enhances anti-counterfeiting security.

[0102] In addition, the multi-stimulus responsiveness of lanthanide-alginate fibers can be used to provide a variety of anti-counterfeiting strategies. Fig.12 As shown in Figure 5, the first layer of anti-counterfeiting is based on the different appearance of the fiber under natural light and UV light. Subsequent anti-counterfeiting is introduced through responsive behaviors to environmental stimuli, such as fluorescence quenching in acidic atmospheres, fluorescence recovery in alkaline atmospheres, and selective response to iron ions. These multiple response mechanisms provide a comprehensive anti-counterfeiting strategy that can greatly enhance the anti-counterfeiting properties of fiber materials.

[0103] This application successfully uses wet spinning technology to prepare multicolor luminescent lanthanide-alginate fibers. Lanthanide ions act as both ionic crosslinkers and luminescent agents in this process. The fibers exhibit excellent uniformity, thermal stability and processability, which are crucial for their practical application in the textile industry. Fibers with different molar ratios of lanthanide ions can emit red, orange and green fluorescence under 254-nanometer ultraviolet light and can be woven into various flexible anti-counterfeiting patterns. In addition, their fluorescence can be quenched in an acidic environment or by iron ions, providing multiple anti-counterfeiting effects. This application provides new insights into the development of flexible anti-counterfeiting technology and smart textiles by using bio-based fibers doped with lanthanide elements.

[0104] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable ordinary technicians in the field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made based on the essence of the content of the present invention should be included in the protection scope of the present invention.

Claims

1. A luminescent lanthanide-alginate fiber, characterized in that: It is made of sodium alginate and LnCl3 through a wet spinning process. The fibers are cylindrical, have no cracks on the surface, and have red, orange and green fluorescence emissions.

2. A luminescent lanthanide-alginate fiber according to claim 1, characterized in that: The fibers contain terbium and europium in different molar ratios, The cross section of the fiber is porous. The raw materials also include ligands.

3. A method for preparing a luminescent lanthanide-alginate fiber according to any one of claims 1 to 2, characterized in that: The sodium alginate aqueous solution is loaded into the spinning syringe and extruded into a coagulation bath containing LnCl3 and 2,2'-bipyridine at an extrusion rate of 2 mL / min. Hydrogel fibers are rapidly generated after the spinning solution contacts the coagulation bath. After about 2 minutes, the fibers are taken out of the coagulation bath and air-dried at room temperature to obtain lanthanide-alginate fibers.

4. The method for preparing a luminescent lanthanide-alginate fiber according to claim 3, characterized in that: The molar ratio of terbium to europium in LnCl3 is 0:10, 3:7 or 10:

0.

5. The method for preparing a luminescent lanthanide-alginate fiber according to claim 3, characterized in that: The concentration of the sodium alginate aqueous solution is 1 wt %, and the concentration of LnCl 3 and 2,2'-bipyridine is 10 mM.

6. The method for preparing a luminescent lanthanide-alginate fiber according to claim 3, characterized in that: The inner diameter of the spinning syringe is 0.7 mm.

7. Use of a luminescent lanthanide-alginate fiber according to any one of claims 1-2, wherein the fiber is prepared by the method according to any one of claims 3-6, characterized in that: The fiber is used for anti-counterfeiting, including flexible anti-counterfeiting.

8. The use of a luminescent lanthanide-alginate fiber according to claim 7, characterized in that: Fibers with three different Tb / Eu molar ratios of 0:10, 3:7 or 10:0 exhibited red, orange and green fluorescence under 254 nm UV light.

9. The use of a luminescent lanthanide-alginate fiber according to claim 7, characterized in that: The luminescence of the fiber is weakened when it is exposed to an acidic environment, and is restored in an alkaline environment.

10. The use of a luminescent lanthanide-alginate fiber according to claim 7, characterized in that: The fibers luminesce less when exposed to ferric ions.

Citation Information

Patent Citations

  • Preparation method of alginate / CdTe fluorescent nanocrystalline composite fluorescent fiber

    CN103147166A

  • Nano phase change and energy storage luminescent fibers and preparation method thereof

    CN104389046A

  • Alginic acid fluorescent fiber material and preparation and application

    CN105155038A

  • A preparing method of a silk fabric with adjustable fluorescence colors

    CN105839404A

  • Double-wavelength fluorescent anti-counterfeiting fiber and manufacturing method thereof

    CN110106574A